Minimalist Program Related to Collocation in Kurdish Language (Raparin Journal of Humanities (RJH), 2025)
This study is devoted to framing  of how to describe "Minimalist Program Related to Collocation in Kurdish Language", aiming to address and analyze the history, principles, the detail of the Program and its distinguished characteristics from the previous stages of Generative and Transformation Grammar, along with the specifying of the most significant modifications and transitions. Furthermore, it analysis the use of the Program in the correct syntactical representation of collocation, whereas up to date; Studies and researches on language and linguistics in Kurdistan has been regarded as a hobby. In other words, little systematic research has been conducted on collocation and its principles.      Based on the foregoing principles, this paper aims to examine and explore certain aspects of a new stage of Generative and Transformation Grammar, which is “Minimalist Program”, and how to apply it on collocation in Kurdish language.      The Research is conducted according to the (Descriptive Analysis) Approach in the light of Chomsky's production theory. And; the research components are derived from the Central Kurmanji- Slemani dialect. In order to achieve this scientific purpose, the research has been divided into three Chapters:    The First section focuses on "Some Theoretical Aspects and the map of Minimalist Program", and the Second section is dedicated to "Transitions and Some Principles of Minimalist Program", while the Third section which is the final section of this study, Collocation in the Framework of Minimalist Program practically has been explored.      In this research, the Introduction, the Results and the bibliography, along with this Abstract are presented in a very scientific order.